Keberlanjutan Bisnis Pupuk Cair Organik PT Alove Bali Desa Saba, Kecamatan Blahbatuh, Kabupaten Gianya - S. A. Widnyani; Wayan Windia; I G.A.A Ambarawati (Universitas Udayana, 2015)
The application of Tri Hita Karana concept become an important issue to ensure the business word existence howadays. The business word will not be developed without concerning the condition and situasion of sosial business environment so that the implementation of Tri Hita Karana becoming a necessity to support the business activities for the companies. It is not just a responsibility but also aduty in the bussiness word. The implementation of Tri Hita Karana concept should become a part of business role an it belong to business policy, so that the business world is a not an organization that is oriented to ward achieving maximum profits but also becomes a learning organization, where the individues that involved have social awareness and process sense not only for the organization environment but also for the sosial environment where the business is located. The purpose of this study is to determine the continuity apotential business of organic liquid fertilizer based on the concept of Tri Hita Karana. The research was conducted to the company that is focused in aloe vera manufacturer. The research is located in Banjar Tengah, Saba village, Blahbatuh, Gianyar regency. The respondents are chosen by census method. That is all the managements and employees of PT Alove Bali. They are 21 people in total. The research is using inverse matrix analysis. Based on the result retrieved, the implementation of Tri Hita Karana in PT Alove Bali is belonging to the quite well category by achieving 38,68% score. The achieving score indicated the sustainability potential value of PT Alove Bali,that are : a). Gatra Parhyangan, PT Alove Bali didn’t have daily religious rituals possibility, b). Gatra Pawongan, PT Alove didn’t give awards for the potential employees, it took a less concern to the social activities in the village. It give a less routinity education for the employees, lack of the external human resource development activities, lack of implementation of routinity internal, meeting, lack of updating regular development information far the company. c). The lack of supplying production tools. The use of production process waste in this case, the lack of maintaining and preserving environment activities, the lack of innovation and technology in developing the products to be develop in the future. The implementation of Tri Hita Karana in PT Alove Bali could be more enharced through the sosialitation of Tri Hita Karana to be more implemented in the business activities and looking fot the solution for the problems in implementing Tri Hita Karana.